IPTEKS EVALUASI SISTEM AKUNTANSI PENGGAJIAN PEGAWAI NEGERI SIPIL PADA DINAS LINGKUNGAN HIDUP DAERAH PROVINSI SULAWESI UTARA - Ponto, Monica T.; Alexander, Stanly W. (Universitas Sam Ratulangi, 2018)
One of the most important factors in office or agency work activities is salary. And within government institutions, each expenditure needs to be recorded as it should include employee salaries. Payroll Accounting System is made for Civil Servants. Sometimes there are problems that may occur during the salary disbursement procedure, namely how this research is conducted to see and evaluate whether the Payroll Accounting System in Environmental Services has been running well or not. After being seen and evaluated, the payroll accounting system in the office environment has basically been running well, effectively and efficiently. There are only a few things that must be considered when taking signatures from Authorized Officers and Budget Users. The procedure must be carried out immediately so that it can be ascertained when taking the signature of the Budget User & Commitment Making Officer in the office, not on official travel.Keywords: Payroll Accounting System, Budget, effectively